1998
DOI: 10.1073/pnas.95.20.11846
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone-related protein is required for tooth eruption

Abstract: Parathyroid hormone (PTH)-related protein (PTHrP)-knockout mice die at birth with a chondrodystrophic phenotype characterized by premature chondrocyte differentiation and accelerated bone formation, whereas overexpression of PTHrP in the chondrocytes of transgenic mice produces a delay in chondrocyte maturation and endochondral ossification. Replacement of PTHrP expression in the chondrocytes of PTHrP-knockout mice using a procollagen II-driven transgene results in the correction of the lethal skeletal abnorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
204
1
9

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(221 citation statements)
references
References 29 publications
7
204
1
9
Order By: Relevance
“…It is clear from the enormous literature on the so-called anabolic and catabolic effects of PTH and PTHrP in vivo that PTH and PTHrP are capable of regulating the formation and/or activities of osteoblasts and/or osteoclasts. However, it also has been shown that in the microenvironment of the tooth during its eruption phase PTHrP drives completely uncoupled osteoclastic bone resorption via the mediation of mesenchymal PTH1R-bearing cells rather than osteoblasts [40]. Thus, at present, the most appropriate interpretation would appear to be that PTHrP may be able to drive either osteoblastic or osteoclastic activity/recruitment, or both, and that the seeming enigma of PTHrP function at bone surfaces might prove to have as its basis similar biological mechanisms to those that underlie the anabolic and catabolic activities of the PTH/PTHrP peptides in the general skeleton.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear from the enormous literature on the so-called anabolic and catabolic effects of PTH and PTHrP in vivo that PTH and PTHrP are capable of regulating the formation and/or activities of osteoblasts and/or osteoclasts. However, it also has been shown that in the microenvironment of the tooth during its eruption phase PTHrP drives completely uncoupled osteoclastic bone resorption via the mediation of mesenchymal PTH1R-bearing cells rather than osteoblasts [40]. Thus, at present, the most appropriate interpretation would appear to be that PTHrP may be able to drive either osteoblastic or osteoclastic activity/recruitment, or both, and that the seeming enigma of PTHrP function at bone surfaces might prove to have as its basis similar biological mechanisms to those that underlie the anabolic and catabolic activities of the PTH/PTHrP peptides in the general skeleton.…”
Section: Discussionmentioning
confidence: 99%
“…Sections were prepared either by CryoJane or routine paraffin techniques [13]. These were stained by H & E, tartrate-resistant acid phosphatase (TRAP), or alkaline phosphatase (via Sigma kit 86-R or in-house reagents in the YCCMD, using either fast red LB or fast blue BB salt to generate red or blue reaction products, as described [21][22][23]). Sections from X-gal-and TRAP-stained specimens of control and unloaded MCL insertions from three mice were analyzed histomorphometrically for the numbers of stain-positive cells using the Osteomeasure system software and hardware.…”
Section: Specimens Sectioning and Stainingmentioning
confidence: 99%
“…This syndrome is produced when tumor-derived PTHrP enters the circulation and stimulates the PTH/PTHrP receptor (Ppr) in bone and kidney, resulting in hypercalcemia . PTHrP-induced activation of the Ppr regulates the morphogenesis of several organ systems, including the endochondral bone, tooth, hair follicle, and vasculature (Karaplis et al, 1994;Philbrick et al, 1998;Maeda et al, 1999;Cho et al, 2003). Consistent with this role, PTHrP and the Ppr are often expressed at relatively high levels within discrete regions of developing organs (Lee et al, 1995;Dunbar et al, 1998;Philbrick et al, 1998).…”
Section: Introductionmentioning
confidence: 87%
“…Mice lacking a functional parathyroid-hormone-related protein (PTHrP) gene die at birth due to premature ossification of the rib cage. However, genetic rescue experiments performed by the crossing of col II-PTHrP transgenics with PTHrP mutants survive and show a failure in tooth eruption (Philbrick et al, 1998). Recently, it has been shown that knockout mice devoid of the osteoclast differentiation factor (ODF) gene, a gene that is required for osteoclast formation and activation, have unerupted teeth (Kong et al, 1999).…”
Section: (A) Eruption Moleculesmentioning
confidence: 99%